Urban socio-economic segregation and income inequality A global perspective - Janssen, Heleen; Tammaru, Tiit; Ubareviciene, Ruta; Van Ham, Maarten (Springer, 2021)
The book "Urban Socio-Economic Segregation and Income Inequality: a Global Perspective" investigates the link between income inequality and residential segregation between socio-economic groups in 24 large cities and their urban regions in Africa, Asia,Australia, Europe, North America, and South America. Author teams with in-depth local knowledge provide an extensive analysis of each case study city. Based on their findings, the main results of the book can be summarised as follows.Rising inequalities lead to rising levels of socio-economic segregation almost everywhere in the world. Levels of inequality and segregation are higher in cities in lower income countries, but the growth in inequality and segregation is faster in cities in high-income countries, which leads to a convergence of global trends. In many cities the workforce is professionalising, with an increasing share of the top socio-economic groups. In most cities the high-income workers are moving to the centre or to attractive coastal areas, and low-income workers are moving to the edges of the urban region. In some cities, mainly in lower income countries, high-income workers are also concentrating in out-of-centre enclaves or gated communities. The urban geography of inequality changes faster and is more pronounced than citywide single-number segregation indices reveal. Taken together, these findings have resulted in the formulation of a Global Segregation Thesis